CAMPUR KODE DALAM LIRIK LAGU MILIK JKT48 KARYA YASUSHI AKIMOTO - Siagian, Elizabeth; Meidariani, Ni Wayan; Meilantari, Ni Luh Gede (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This research aims to determine the form of code mixing and the factors that cause code mixing in the lyrics of the song JKT48 by Yasushi Akimoto. In this research using sociolinguistic theory. Then, this research uses data collection methods and techniques used are the listening method and the note-taking technique. Methods and techniques of data analysis using descriptive qualitative method. This research uses the method of presenting the results of data analysis informally. Based on the results of the analysis, it was found that there were several forms of code mixing including the insertion of word elements, the insertion of phrase elements, the insertion of repetition of words, and the insertion of sentence elements. There are factors that cause code mixing, including because there are no appropriate words to explain the word and informal situation factors.